ONLINE LICENSING APPLICATION SYSTEM DESIGN FOR CV. FILADELPHIA TIRTA PERKASA USES CODEIGNITER AND BOOTSTRAP FRAMEWORK - Nurdiyanto Yusuf; Dwi Kartinah (Asosiasi Dosen Muda Indonesia, 2023)
A website can be interpreted as a document stored on a web server that has a certain type and topic. Websites consist of two types, namely static and dynamic websites. A static website is a website where users cannot change the content of the website directly using a browser. Meanwhile, in a dynamic web, the interactions that occur between users and servers are very complex. One can change the content of a particular page by using a browser. This website application was built with the PHP, CSS, HTML and JavaScript programming languages using the Codeigniter 3.0.6 and Bootstrap 3.3.6 framework. This application was created to make it easier for an employee to get a CV. Filadephia Tirta Perkasa in applying for leave and permission. The research method used is the Waterfall method which consists of planning and needs analysis, design, implementation, testing, installation and maintenance stages. The application is divided into two designs, namely an application for administrators and an application for employees. Based on the implementation and results of trials carried out, it shows that this application can run well and can display all pages.